2017
DOI: 10.1200/jco.2016.72.0748
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Nomograms Predictive of Overall and Progression-Free Survival in Patients With Oropharyngeal Cancer

Abstract: Purpose Treatment of oropharyngeal squamous cell carcinoma (OPSCC) is evolving toward risk-based modification of therapeutic intensity, which requires patient-specific estimates of overall survival (OS) and progression-free survival (PFS). Methods To develop and validate nomograms for OS and PFS, we used a derivation cohort of 493 patients with OPSCC with known p16 tumor status (surrogate of human papillomavirus) and cigarette smoking history (pack-years) randomly assigned to clinical trials using platinum-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(164 citation statements)
references
References 23 publications
7
153
0
1
Order By: Relevance
“…In previous studies, multifocal lesions, large tumor size, advanced neoplasm grade, and high serum AFP level have been reported to increase the possibility of vascular invasion in advanced HCC (33)(34)(35). In the present study, abnormal AFP level, an independent risk factor for MVI, was also significantly associated with MVI.…”
Section: Discussionsupporting
confidence: 68%
“…In previous studies, multifocal lesions, large tumor size, advanced neoplasm grade, and high serum AFP level have been reported to increase the possibility of vascular invasion in advanced HCC (33)(34)(35). In the present study, abnormal AFP level, an independent risk factor for MVI, was also significantly associated with MVI.…”
Section: Discussionsupporting
confidence: 68%
“…18 While these trials included patients with HNC of multiple subsites, only patients with OPSCC were used to generate this model. This data source is advantageous in that patient, treatment, and outcome data would be expected to be relatively homogenous, complete, and accurate.…”
Section: Discussionmentioning
confidence: 99%
“…We identified four calculators: one developed at the MAASTRO Clinic (“MAASTRO”), 20 one based on data from Radiation Therapy Oncology Group (RTOG) trials (“RTOG”), 18 one based on patients treated in eastern Denmark (“Denmark”), 19 and one developed at Erasmus Medical Center (EMC) (“Erasmus”). 21, 23 Table 1 summarizes the data sources of each calculator, with additional details provided in Supplemental Tables 1–4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing a compendium of previously-published data, Lau and Iyengar take the novel approach of focusing on weight loss in cancer patients who are receiving radiation [6]. Only recently, Fakhry and others added yet another such study that looks at radiation in over 600 patients with oropharyngeal cancer and observed that weight loss is associated with shorter cancer progression-free survival [7]. Such studies join countless others that have reached the exact same conclusion: weight loss in cancer patients is associated with poor clinical outcomes.…”
mentioning
confidence: 99%